Gây u thực nghiệm trên chuột bằng DMBA (7,12 Dimethyl benz[A] anthracene) - Thảo, Đỗ Thị; Phương, Đỗ Thị; Cúc, Nguyễn Thị; Nga, Nguyễn Thị; Trang, Nguyễn Thị (VNU Journal of Science: Natural Sciences and Technology; Vol 25 No 2, 2009)
Abstract